آليات استيعاب الآخر في ضوء السيرة النبوية ودورها في إحلال السلام العالمي: دراسة تحليلية للمواقف النبوية في العهد المدني: Prophetic Mechanisms of Accommodating the Other and Their Role in Global Peace: An Analytical Study of the Medinan Era - قول معمر (الدراسات الإسلامية, 2025)
This study investigates the contemporary relevance of the teachings of Prophet Muhammad (PBUH) during the Medinan period as a solution to modern global crises. The study posits that modern civilization, built on material foundations, conflict-oriented values, self-interest, and racism, has led to a profound moral and spiritual crisis, fracturing communication bridges and fueling wars between Eastern and Western peoples. It suggests that the Prophetic biography (Sirah) in Medina offers a "comprehensive framework for accommodation" and a practical model for managing differences and achieving world peace. The key mechanisms of Prophetic accommodation examined are: the construction of the Mosque (Masjid) as a spiritual and civilizational beacon that dissolves social distinctions and establishes equality and unity; the Charter of Brotherhood (Mu’akhat) between the Emigrants (Muhajirun) and the Helpers (Ansar), which embodied a unique concept of human solidarity, altruism, and rejected individualism and selfishness; and the Constitution of Medina, which founded a modern civil state by elevating the bond of one nation (Ummah Waahidah) above ethnic and sectarian ties, and established the recourse to God and His Messenger (Shari’ah) as the ultimate reference point for resolving disputes.